Image encryption based on a combination of multiple chaotic maps - Elkandoz, Marwa Tarek; Alexan, Wassim (Multimedia tools and applications, 2022)
Recent years have seen a rapid evolution of digital communications and an immense use of image transmissions over unsecured links. More specifically, some domains require the exchange of images depicting sensitive information, such as fingerprints, medical records and government or military satellite images. This creates a major challenge for researchers to come up with efficient and effective image encryption schemes. On the other hand, chaotic maps have proven suitable for such applications. This is because they exhibit characteristics such as ergodicity and sensitivity to control parameters and initial conditions. In this paper, an image encryption confusion-diffusion technique is proposed. First, the image pixels are disarranged resulting in a shuffled one which is then diffused through XORing its pixels with a secret key. This key is generated from a combination of different chaotic maps. Performance of the proposed scheme is evaluated utilizing various metrics. The proposed scheme is shown to be robust against differential attacks and resistant to statistical attacks. Its running time is very small which guarantees its efficiency and suitability for real time applications.